(untitled) (Medical Forum Monthly, 2025)
Objective: To ascertain the frequency of Doppler-confirmed foot ischemia in individuals with type 2 diabetes mellitus (T2DM) and assess its correlation with glycemic control, treatment strategy, comorbid conditions, and disease duration. Study Design: Analytical-Cross Sectional Study Place and Duration of Study: This study was conducted at the Dr. Ruth K.M. Pfau Civil Hospital in Karachi between September 2024 and February 2025. Methods: Consecutive sampling was used to select 107 individuals with type 2 diabetes mellitus (T2DM), ranging in age from 30 to 80. Comorbidities, treatment type, length of illness, and HbA1c levels were among the information gathered. Following lower-limb Doppler ultrasonography, arterial flow was classified as either normal (triphasic) or abnormal (biphasic/monophasic) for each participant. The Chi-square and independent t-tests were used in the statistical analysis, which was carried out using SPSS version 25. A p-value of less than 0.05 was deemedstatistically significant. Results: Among the 107 participants, 78 (72.9%) had abnormal Doppler flow (mean age 56.8 ± 10.2 years; 55.1% male), according to the results. Poor glycaemic control (HbA1c ≥ 7%) was found to be significantly correlated with abnormal flow (p = 0.03). The mean length of diabetes was longer in patients with ischaemic changes (12.6 ± 6.1 years vs 8.4 ± 5.7 years; p = 0.02). Abnormal flow was more common in oral hypoglycemic users (83.6%) than in insulin users (67.6%), though this difference was not statistically significant (p = 0.11). Conclusion: Most people with type 2 diabetes mellitus had subclinical foot ischaemia, especially those with longer disease duration and poorer glycaemic control. For prompt management and the avoidance of major ischaemic complications, routine Doppler evaluation is highly recommended.